Leveraging best practices in data governance: An organization-wide data inventory and mapping project to support a five year data strategy. (2018) - Travers, Joseph; Campitelli, Crystal; Light, Richard; Sa, Eric de; Stabile, Julie; Iron, Karey
No abstract available